INFLUENCE OF PHARMACOLOGICAL CORRECTION OF MAGNESIUM DEFICIENCY ON PSYCHOLOGICAL STATUS AND FUNCTIONAL-BIOCHEMICAL INDICATORS IN YOUNG MEN - Bilovol, O.M.; Kniazkova, I.I.; Kіrienko, O.M.; Mishchenko, V.M.; Kuzminova, N.V.; Kіrienko, D.О.; Abramova, L.P. (World of Medicine and Biology, 2025)
The purpose of the study was to evaluate the effect of magnesium deficiency correction with magnesium orotate therapy on anxiety levels, diastolic function parameters, and physical performance in young men. Seventy-six young men (mean age 28.5±5.5 years) without cardiovascular pathology and any somatic diseases in their medical history were examined, among whom 51.3 % were diagnosed with hypomagnesemia, of whom 20 (group 1) were prescribed magnesium orotate (32.8 mg of magnesium) (Magnorot, “Wörwag Pharma”, Germany) at a dose of 500 mg three times a day. Group 2 consisted of 19 individuals who were not prescribed magnesium supplements. The study lasted 8 weeks. It was found that a significant proportion of the young men examined had a significant decrease in serum magnesium concentration, along with increased anxiety, signs of diastolic dysfunction, and decreased physical performance. It was shown that 8 weeks of magnesium orthoate therapy helped achieve target serum magnesium levels, along with improved diastolic function, a positive effect on physical performance, and a reduction in reactive and personal anxiety levels to normal values. It was determined that the addition of magnesium orotate to young men for 8 weeks was safe; no adverse events were reported.
Keywords: serum magnesium content; hypomagnesemia; anxiety; diastolic function; physical performance; young men; magnesium orotate